Diversity of Antarctic microorganisms - potential producers of biologically active substances - T. O. Kondratiuk; T. V. Beregova; L. I. Ostapchenko (Ukrainian Antarctic Journal, 2016)
Search for new producers of biologically active compounds that can be widely used in various fields of human activity is intense among the variety of organisms, habitats of which are connected with the extreme conditions of existence, including Antarctica. The purpose of this work was conducting relevant research on this topical issue. 25 isolation of pure cultures of microscopic fungi (species of Mortiriella, Mucor, Eurotium, Cladosporium, Fusarium, Geotrichum, Pseudogymnoascus, Penicillium, Phoma, Rhodotorula etc.) were obtained from the samples of mosses, lichens, soil and stones obtained from 18-20th Ukrainian Antarctic expedition (Galindez, Pitterman, and Yalur Islands). Among them Pseudogymnoascus pannorum and Mucor circinelloides are characterized by a pronounced activity to the synthesis of complex of biologically active lipids. 8 pure cultures of bacteria were also isolated that synthesize biologically active substances which can inhibit the growth of other microorganisms (pronounced antagonistic properties were observed). Collection of technologically advanced microorganisms replenished with new srains of microscopic fungi and bacteria - producers of biologically active compounds.